Estudio de caso: GlaxoSmithKline Perú - Flores Uzategui, Claudia Jeaneth (2018)
The following research was done through the empirical method. In it, will be described and evaluated the context in which the british pharmaceutical company GlaxoSmithKline Peru is today, emphasizing the problem that the business unit: consumer healthcare, is going through. It will specify and question the problem that currently exists in the commercial area of the company and how it affects the sales of the business. In addition, the situation that the pharmaceutical industry is currently facing will be explained, as well as the difficulties and trends that have arisen in the Peruvian state recently.